Students’ English Language Anxiety In Indonesian EFL Classroom - Munir, Mawarwati (Celebes Journal of Elementary Education, 2024)
Foreign Language Anxiety is considered as one of factors that might hinder learners to perform well during the learning process in English as a Foreign Language classroom. The objectives of this study was to explore Factors causing language anxiety of EFL students in classroom presentation and students’ strategy to overcome their language anxiety in EFL classroom presentation. This research applied qualitative case study research method. The participants of this research were the students of English education department of under graduate Program of State Islamic University of Alauddin Makassar. The data were obtained from the questionnaire, classroom observation and interview. Based on the result of the study showed the factors causing language anxiety of EFL classroom presentation, those are: Psychological factors and Linguistics factors. Which is the Psychological factors consist of nervousness, fear of making mistake, lack of confident, and shyness and Linguistics factors consist of poor of pronunciation and lack of proficiency. This also delivered a student’s ways to overcome their language anxiety, those are pedagogic strategy and digitalizing Strategy.